Genetic influences on hub connectivity of the human connectome - Aurina Arnatkeviciute (Nature Portfolio, 2021)
How genes sculpt the complex architecture of the human connectome remains unclear. Here, the authors show that genes preferentially influence the strength of connectivity between functionally valuable, metabolically costly connections between brain network hubs.